PEMODELAN TIGA DIMENSI ANOMALI GRAVITASI DAN IDENTIFIKASI SESAR LOKAL DALAM PEMENTUAN JENIS SESAR DI DAERAH PACITAN - Alexander Felix Taufan Parera; I Gusti Ketut Satria Bunaga; Mahmud Yusuf (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Indonesia region is one of area which have the highest vulnerability level of earthquake occurrence. Not only the mid ocean earthquakes but also the fault activities on crustal zone are very dangerous. Now, these fault activities are become special interest after the Jogja 2006 earthquake occurred. The same event occurred on February 2011 that the earthquake happened on Pacitan region with the epicenter location was around in the Grindulu fault track. Because of that, that existence is needed to study especially under the structure modelling using GRAV3D software and Second Vertical Derivative method (SVD).Study results show that two segments of the fault leads NE-SW which have normal fault pattern with slight oblique and transform fault pattern. Besides, this study results show the difference of density value in the area of the fault that have depth variation until six kilometer.   Keywords: GRAV3D, Second Vertical Derivative.